801 Middle Meningeal Artery Embolization Versus Conventional Treatment of Chronic Subdural Hematomas. (1st April 2022) - Enriquez-Marulanda, Alejandro; Gomez-Paz, Santiago; Salem, Mohamed M.; Mallick, Akashleena; Arle, Jeffrey E.; Stippler, Martina; Papavassiliou, Efstathios; Alterman, Ron L.; Ogilvy, Christopher S.; Moore, Justin M.; Thomas, Ajith J.
Abstract : INTRODUCTION: Middle meningeal artery (MMA) embolization is an emerging minimally invasive endovascular technique for chronic subdural hematoma (cSDH). Currently, limited amount of literature exists on its safety and efficacy compared with conventional treatment (open-surgical-evacuation-only). METHODS: Retrospective analysis of patients with cSDHs treated with MMA embolization in a single center from 2018-2019 was performed. Comparisons were made with a historical conventional treatment cohort from 2006-2016. Propensity score matching (PSM) analysis was used to assemble a balanced group of subjects. RESULTS: A total of 357 conventionally treated cSDH and 45 with MMA embolization were included. After balancing with PSM, a total of 25 pairs of cSDH were analyzed. Comparing the embolization with the conventional treatment group yielded no significant differences in complications (4% vs. 4%; p>0.99), clinical improvement (82.6% vs. 83.3%; p=0.95), cSDH recurrence (4.3% vs. 21.7%; p=0.08), overall re-intervention rates (12% vs. 24%; p=0.26), mRS >2 on last follow-up (17.4% vs. 32%; p=0.24) as well as mortality (0% vs. 12%; p=0.09). Radiographic improvement at last follow-up was significantly higher in the open surgery cohort (73.9% vs. 95.6%; p=0.04). However, there was a trend for lengthier last follow-up for the historical cohort (72 vs. 104 days; p=0.07). CONCLUSIONS: There was a trend for lower recurrence and mortality rates in the embolization era cohort. There were significantly higher radiological improvement rates on last follow-up in the surgical only cohort era. There were no significant differences in complications and clinical improvement.